Low-level red light inhibits human retinal pigment epithelial cell fibrosis via UBE2C in a myopia-simulating hypoxic microenvironment - Yaping Gao; Xiaowei Zhu; Yulan Luo; Xuefen wu; Ling Tan; Haijiang Qiu (European Journal of Medical Research)
Abstract Background Low-level red light (LLRL) irradiation may inhibit myopia occurrence and progression. Understanding how LLRL inhibits fibrosis in human retinal pigment epithelial (hRPE) cells is critical to inhibiting myopia progression and developing novel therapeutic strategies. Here, we explored the effects of LLRL on hRPE cells in a myopia-simulating hypoxic microenvironment and elucidated the mechanisms through which it inhibits scleral remodeling. Methods We first used the MTT assay to analyze hRPE cell proliferation under hypoxic conditions after LLRL irradiation at varying frequencies over different durations. RNA sequencing was used to screen for key signaling molecules leading to hRPE cell fibrosis. Western blotting, reverse transcription quantitative polymerase chain reaction, and immunofluorescence assay were used to detect the role of ubiquitin binding enzyme E2 C (UBE2C) in hRPE cell fibrosis under LLRL irradiation. Results LLRL was noted to regulate the extracellular matrix, inhibiting fibrosis in hypoxic hRPE cells. Moreover, supernatant of LLRL-treated hypoxic hRPE cells inhibited scleral remodeling in human scleral fibroblasts. Mechanistically, LLRL inhibited cell fibrosis by regulating UBE2C activation of the AKT/mTOR pathway. Conclusion In a hypoxic environment, LLRL irradiation can prevent fibroblast transformation in hRPE cells, indicating its potential in scleral remodeling inhibition. Our results revealed the molecular mechanism through which red light controls myopia and provide evidence for further basic and clinical research. Graphical abstract